PERANCANGAN VIDEO PROMOSI OBJEK WISATA GOA BATU KAPAL DI KABUPATEN SOLOK SELATAN - SITI FATIMAH, Dr. M. Nasrul Kamal, M.Sn., (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of the promotional video designer explains the history and uniqueness that exist in Goa Bau Kapal Tourism Balai Janggo, South Solok Regency, West Sumatra Province as the main media design in addition to other supporting media.Goa Batu Kapal Tourism is located in Jorong Sungai Kunyit Balai Janggo in South Solok Regency. Due to the lack of information, and the lack of effective information obtained so far, so many people or tourists who do not know about the tour of stone cave ships located in Nagari Balai Janggo, Solok Selatan Regency, West Sumatra Province, for this reason, the authors designed a promotional video for rock cave tours. in South Solok Regency. To increase the number of visitors back to the rock cave cave tour, video is the main media for design, in addition to video there are a number of supporting media to support this video in the rock cave cave promotion so that the target audience is interested in the form of Poster, CD Cover, CD Label, Key Chain, Pin, T-shirt and TotebaThe methodology used for design is 5w + 1h which is used as a basic concept of problem solving, namely (what) what, who (who), when (where), why (why) and how (how). This 5W + 1H analysis is to illustrate the results of the analysis used as the basis or basis for preparing objectives and strategies in designing promotional videos. Then all aspects that are summarized of natural tourism in South Solok Regency can be packaged into promotional video media, so the South Solok Regency natural tourism promotion video can be an effective and communicative media.Keywords: media promotion, nature tourism, legend tourism, Goa Batu Kapal Balai Janggo